Millennial’s Investment and Debt Behavior - Hartina, Evita; Widyastuti, Umi; Nazir Ahmad, Gatot (International Journal of Social Science, Education, Communication and Economics, 2024)
This study examines the varying influences that Indonesian Millennial Generations bring to the relationship between behavior and views toward finance and their intentions for investments and debts. Financial literacy, risk perception, materialism, emotion, and religiosity are all influencing factors. 200 people participated in a quantitative method survey used in the methodology study. Using Smart-PLS version 4, SEM analysis is used to test the hypothesis. The findings of the study indicate that there is a significant relationship between financial literacy and both investment and debt intention. In addition, materialism has an impact on investment intention, while religiosity has an impact on debt investment. Aside from that, there is no influence from Religion, Emotion, or Risk Perception on Investment Intention; however, Materialism, Emotion, and Risk Perception do influence Debt Intention.